Lean In: Women, Work, and the Will to Lead - Amanda Blanco (Journal of Financial Therapy, 2015)
Lean In: Women, Work, and the Will to Lead is a self-proclaimed “sort of feminist manifesto” written to empower women and men. Sandberg gives insight into how to overcome and help others overcome the internal and external obstacles that may hinder success. This book is recommended for women in the financial services field, as women are underrepresented in certain segments of financial services.
Keywords: book review; women; leadership